University Rankings: Quality, Size and Permanence - Bejan, Adrian; Gunes, Umit; Sahin, Bahri (CAMBRIDGE UNIV PRESS, 2020)
Why are the rankings of universities not changing? Why is the demographic composition of top universities the same? In this review, these questions are addressed based on physics. Although size matters, higher ranks do not correlate with bigger sizes. The higher ranks belong to universities that have more authors who receive more citations. Citations are a record of how ideas spread from the source to the whole globe, in accordance with the physics of the logistics S-curve phenomenon. The spreading occurs in three periods - slow, fast, slow - and the population served by each idea during its lifetime depends on the size of the first big channel that carries the idea. An idea from a famous university has a larger spreading territory around it than an idea from a lesser-known university. Creativity is key: rankings come from visibility through citations, and, in turn, visibility for an author is aided by the higher visibility of the university. The demographic composition of the top universities is the same: for instance, the percentage of female authors and authors of East Asian origin among the 200 most cited authors does not vary significantly over the 20 highest ranked universities.
Keywords: CONSTRUCTAL LAW; ADRIAN BEJAN; DESIGN; EVOLUTION; PHYSICS; THERMODYNAMICS; BEHAVIOR; Area Studies